Ketidakadilan Gender Dalam Novel Secuil Hati Wanita Di Teluk Eden Karya Vanny Chrisma W - Birahmatika Zaidan Prassetio; Putriyanasari (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Ladies are images of life, frequently encountering treachery and savagery since they were born ladies. Writing is one of the media that tells almost numerous things in life, counting women's lives. Within the perusing content of the novel A Little Heart of Ladies within the Inlet of Eden by Vanny Chrisma W is utilized as a investigate source. This think about points to describe the frame of gender bad form of the most culprit and the most character's resistance to persecution within the novel A Small Heart of Ladies in Eden Cove by Vanny Chrisma W. The inquire about strategy utilized could be a descriptive method of subjective shape with a women's activist scholarly feedback approach. Based on the comes about of information investigation, the most character's sexual orientation treachery was concluded: 1) Treachery within the frame of Generalizations or Negative Labeling, 2) Bad form within the frame of savagery, specifically savagery in physical and non-physical forms.